Penguatan Empati Sosial dan Literasi Ekonomi Anak melalui Edukasi Koperasi Komunitas sebagai Implementasi Kebijakan Diktisaintek Berdampak di Kecamatan Darul Imarah, Aceh Besar - Meri Yulizar rohana; Mauliana Rizki; Nurul Azmi; Dicky Firlanda; Nadhifatul Hawari (Pendidikan Matematika, FKIP Universitas Mataram, 2026)
Social empathy and economic literacy among children in rural areas remain low, thereby hindering community development amid Indonesia’s Dikdasaintek policy, which emphasizes technology-based education and innovation that positively impact society. This study aims to strengthen children’s social empathy and economic literacy through community cooperative education as an implementation of the Dikdasaintek policy within the Community Service Program (KKN) in Punie Village, Darul Imarah District, Aceh Besar. The method employed involved collaborative KKN activities, including workshops on cooperative principles, direct simulations of saving and borrowing activities, and community engagement games attended by 50 elementary school children. The results showed a 35% increase in empathy scores based on pre- and post-surveys and a 42% increase in economic literacy, as evidenced by the children’s ability to independently and responsibly manage a simulated cooperative. Community participation also increased by 60%, encouraging the emergence of sustainable local initiatives to support village community empowerment in the social and economic aspects of local society. In conclusion, the integration of cooperative education into the KKN program effectively implements the Dikdasaintek policy while promoting children’s holistic development and sustainable rural community empowerment.